2020
DOI: 10.1002/2211-5463.12838
|View full text |Cite
|
Sign up to set email alerts
|

miRNA‐765 mediates multidrug resistance via targeting BATF2 in gastric cancer cells

Abstract: Elucidation of the mechanisms underlying multidrug resistance (MDR) is required to ensure the efficacy of chemotherapy against gastric cancer (GC). To investigate this issue, here we identified that microRNA‐765 (miRNA‐765) is up‐regulated both in MDR GC cell lines and in specimens from patients who are not responding to chemotherapy. In addition, down‐regulation of miRNA‐765 increased the sensitivity of GC cells to anticancer drugs, whereas its overexpression had the opposite effect. Moreover, miRNA‐765 suppr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…While Zhu et al validated that LINC00994 repressed the malignant behaviors of pancreatic cancer cells through regulating the miR-765-3p/RUNX2 axis (which means that miR-765 accelerated the development of HCC) [ 41 ]. The oncogenic effect of miR-765 is not only limited to these two tumors, but also plays a similar role in esophageal squamous cell carcinoma [ 42 ], gastric cancer [ 43 ], and osteosarcoma [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…While Zhu et al validated that LINC00994 repressed the malignant behaviors of pancreatic cancer cells through regulating the miR-765-3p/RUNX2 axis (which means that miR-765 accelerated the development of HCC) [ 41 ]. The oncogenic effect of miR-765 is not only limited to these two tumors, but also plays a similar role in esophageal squamous cell carcinoma [ 42 ], gastric cancer [ 43 ], and osteosarcoma [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…An increasing number of studies have reported that the sensitivity of tumor cells to anticancer drugs can be altered by miRNAs (43)(44)(45). miR-34a was reported to enhance the chemosensitivity of PC3 cells to paclitaxel and camptothecin and PCa cells treated with miR-143 showed higher chemosensitivity to docetaxel (37,46).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, suppressing of miR-765 diminished expression of P-gp, LRP, MRP1, and MDR related genes in SGC7901/VCR. Besides, inhibition of miR-765 accumulated cells in G0/G1 phase and induced apoptosis in SGC7901/VCR cells [80]. Previous evidence has revealed that overexpression of Zinc Finger Protein 139 (ZNF139) is related to GC MDR.…”
Section: The Effect Of Mirnas On Multidrug Resistancementioning
confidence: 99%